Penghimpunan Wakaf Uang pada Perbankan Syariah berdasarkan Hukum Positif Indonesia - Syifa Salsabila; Nun Harrieti; Helza Nova Lita (Jurnal Iqtisad, 2022)
Indonesia as a country that embraces dual-banking systems recognizes Conventional Banking and Islamic Banking. One of the differences between the two systems is the social function on Islamic Banking Law. Islamic Banking Law recognizes social functions which one of them is to collect and channel cash waqf as Sharia Financial Institution for Receiving Cash Waqf (SFIRCW) . However, the responsibility that circulates cash waqf shows uncertainty on which party is to be responsible for the cash waqf. The method of writing used in this paper is normative juridical method, which will be linked to the practice of SFRICW on Islamic Banks. The practice for the implementation of SFIRCW can be seen on Bank Muamalat Indonesia (BMI). The practice shows that BMI on receiving Cash Waqf is not responsible for the management and the distribution of the cash waqf, and it is only Nazhir’s responsibility. This shows that Islamic Bank is responsible not only for the SFIRCW function but also the practice of wadi’ah agreement. Islamic Bank is responsible for saving and distributing cash waqf to Nazhir and guarantee that the money is available to be cashed out at all times. Additionally, Nazhir also bears responsibility for guaranteeing that cash waqf practice is carried out according to its means as in Sharia Principle and Rule of Laws.Indonesia merupakan negara yang mengakui dual-banking system yaitu Bank Konvensional dan Bank Syariah. Salah satu perbedaan dari kedua sistem tersebut adalah fungsi sosial pada UU Perbankan Syariah. UU Perbankan Syariah menyebutkan salah satu fungsi sosial adalah menghimpun dan menyalurkan dana wakaf uang sebagai Lembaga Keuangan Syariah Penerima Wakaf Uang(LKS PWU). Namun, pertanggungjawaban atas dana wakaf menimbulkan pertanyaan atas pihak mana yang harus bertanggungjawab atas dana tersebut. Metode penulisan artikel ini menggunakan metode normatif yuridis yang akan dihubungkan dengan praktik LKS PWU pada Bank Syariah. Praktik dari LKS PWU dapat dilihat dari Bank Muamalat Indonesia (BMI), di mana BMI menegaskan bahwa dalam menerima wakaf uang, BMI tidak bertanggung jawab untuk pengelolaan dan penyalurannya, dimana hal tersebut merupakan tanggung jawab Nazhir. Hal ini memperlihatkan bahwa Bank Syariah tidak hanya bertanggungjawab atas fungsi LKS PWU, namun juga praktik dari akad wadi’ah. Bank Syariah bertanggungjawab untuk menghimpun dan menyalurkan dana kepada Nazhir dan menjamin bahwa dana tersebut dapat diambil sewaktu-waktu. Selain itu, Nazhir memiliki tanggung jawab untuk menjamin bahwa praktik wakaf uang dapat dilaksanakan sesuai dengan tujuannya berdasarkan Prinsip Syariah dan Peraturan Perundang-Undangan.